Iran Diabetes Research Roadmap (IDRR) Study; Nutrition in Diabetes: A Review Article - Zarin Sadat EBRAHIMI (Iranian Journal of Public Health, 2017)
Background: The study aim was to reports detailed characteristics of nutrition research in field of diabetes, and recognize knowledge gap in nutrition science in diabetes in Iran.